Degradation of Dyes Using Zinc Oxide as the Photocatalyst - Lee, Kian Mun (2008)
In this study, ZnO was synthesized via precipitation method. The resulting ZnO catalyst was characterised by X-ray Diffraction (XRD), Fourier Transform Infrared (FT-IR), Thermogravimetric Analysis (TGA), Scanning Electron Microscopy (SEM), Particle Size Analysis (PSA) and surface area measurement (BET method). XRD analysis showed that hydrozincite (Zn5(CO3)2(OH)6) was formed during precipitation process and the decomposition of hydrozincite was completed at temperature ~ 400 °C after 2 hours calcination in air. The ZnO produced was spherical in shape (morphology), has a surface area of 25.8 m2g-1and particle size of 255 ± 2 nm with hexagonal crystal structure. The ZnO produced was tested for photodegradation of Methyl Orange (MO), Methylene Blue (MB), and Reactive Orange 16 (RO 16) under the illumination of ultraviolet (UV, λmax = 365 nm) light. Various parameters affecting the degradation performance such as catalyst loading, initial dye concentrations, initial pH, light intensity, different light sources and addition of oxidants was examined. The removal percentage of dyes increased with increasing mass of ZnO up to an optimum mass but decreased with increasing initial concentrations of the dye. Enhanced colour removal for MO, MB and RO 16 was observed when the UV lamp used was changed from 6 to 100 watts. In addition, the highest removal was achieved at pH 11 and addition of H2O2 and K2S2O8 led to an enhancement in the removal of all the three dyes. The photocatalytic degradation of mixed dyes solution (consists of a mixture of MO, MB and RO 16) was conducted and 64.90 % removal was observed. The photodegradation of dyes followed first-order kinetics.